Foreign Trade and Its Effects on Nepalese Economic Development (Journal of Nepalese Business Studies, 2006)
Having with the objectives of understanding the effects of foreign trade on the economic development process of Nepal, this paper attempts to deal the role and the impact of export and import along with many other pertinent factors. The determining factors that have been considered along with export are capital stock, labor force, average propensity to save (APS), relative price index (RPI), ratio of government development expenditure to GDP. Moreover, GDP, PCI, and growth rate of GDP are the assumed development indices. These macro variables are introduced through the application of various econometric models. The empirical results have been estimated by applying annual data for the period of 1974/'75 to 2002/'03. The different models in linear and log-linear forms have justified that exports growth leads to economic growth. Therefore, the policy of adequate investment in export-oriented industries that embody a 'proper mix' of export promotion and import substitutions is suggested.Journal of Nepalese Business Studies Vol.2(1) 2005 pp.13-32